Outcomes of relationship quality in business-to-business contexts: A South African concrete product market perspective - Lehlohonolo Amos Masitenyane; Asphat Muposhi; Bakae Aubrey Mokoena (Cogent Business & Management, 2023)
AbstractBusiness to business (B2B) relationships in South Africa’s concrete product market are characterised as transactional, asymmetrical and adversarial. This study examines the outcomes of relationship quality satisfaction in South Africa’s construction industry. Quantitative data was collected from 560 concrete product suppliers in South Africa. Expectation, involvement and flexibility emerged as the major factors that favourably influence perceptions of relationship quality. Moreover, the study showed low levels of trust, forgiveness, and communication between concrete product suppliers and civil contractors. Increased collaboration, trust and communication are recommended as strategies for managing incidences of conflict. The findings of this study underscored the need by concrete product suppliers (CPS) and civil engineering managers to improve the quality of communication. To be effective, communication should be planned in a manner that is proactive such that market information is timeously shared in a way that minimises risk exposure. Quality communication may also be enhanced by leveraging the power of internet enabled channels, whilst being attentive to reduce incidence of information leakage. The study findings also suggest the need to invest in trust building, since lack of trust breeds uncertainty which compromises project quality.